Decoupling of greenhouse gas emissions from global agricultural production: 1970–2050. (6th January 2016) - Bennetzen, Eskild H.; Smith, Pete; Porter, John R.
Abstract: Since 1970 global agricultural production has more than doubled; contributing 1/4 of total anthropogenic greenhouse gas (GHG) burden in 2010. Food production must increase to feed our growing demands, but to address climate change, GHG emissions must decrease. Using an identity approach, we estimate and analyse past trends in GHG emission intensities from global agricultural production and land‐use change and project potential future emissions. The novel Kaya–Porter identity framework deconstructs the entity of emissions from a mix of multiple sources of GHGs into attributable elements allowing not only a combined analysis of the total level of all emissions jointly with emissions per unit area and emissions per unit product. It also allows us to examine how a change in emissions from a given source contributes to the change in total emissions over time. We show that agricultural production and GHGs have been steadily decoupled over recent decades. Emissions peaked in 1991 at 12 Pg CO2 ‐eq. yr −1 and have not exceeded this since. Since 1970 GHG emissions per unit product have declined by 39% and 44% for crop‐ and livestock‐production, respectively. Except for the energy‐use component of farming, emissions from all sources have increased less than agricultural production. Our projected business‐as‐usual range suggests that emissions may be further decoupled by 20–55% giving absolute agricultural emissions of 8.2–14.5 Pg CO2 ‐eq. yr −1 by 2050, significantly lower than many previous estimates that do not allow for decoupling. Beyond this, several additional costcompetitive mitigation measures could reduce emissions further. However, agricultural GHG emissions can only be reduced to a certain level and a simultaneous focus on other parts of the food‐system is necessary to increase food security whilst reducing emissions. The identity approach presented here could be used as a methodological framework for more holistic food systems analysis.